From defect mode to topological metamaterials: A state-of-the-art review of phononic crystals & acoustic metamaterials for energy harvesting - Akbari-Farahani, Fahimeh; Ebrahimi-Nejad, Salman (Sensors and actuators. A. Physical., 2024)
Recent advances in the field of low-power electronic components production have spurred research in energy harvesting. Ambient sound can be used as a source of energy, and the material through which the sound is emitted can affect the harvested energy. Improving the efficiency of energy harvesting from ambient sound has become a hot topic. Phononic crystals and acoustic metamaterials enhance the harvesting efficiency of piezoelectric materials when deformed by sound waves. The material properties of phononic crystals and acoustic metamaterials can also affect noise control. In this paper, we aim to elaborate on different types of phononic crystals and metamaterials, such as the defect mode metamaterial, Gradient Index (GRIN) system, and topological metamaterial, based on their attractive attributes in the energy harvesting field that show promising phenomena compared to conventional metamaterials. We also summarize the advantages and challenges of these structures and provide some suggestions for future research, such as optimizing the geometry, exploring the potential of topological metamaterials, and combining different mechanisms. The classification proposed in this paper aims to provide a convenient reference for researchers involved in this field, open new horizons, and provide insights for further exploration. [Display omitted] •Comprehensive survey of phononic crystals and metamaterials for energy harvesting.•We discuss various metamaterial structures and their pros and cons for energy harvesting.•Future research suggestions on geometry, topology, and mechanism optimization.•Useful reference and new horizons for phononic crystals and metamaterials research.•Influences of material and geometry on power output efficiency is discussed.